Eutetranychus orientalis Klein (oriental spider mite). Phytosanitary risk analysis for Ukraine - L. Titova; Yu. Klechkovskyi; O. Palahina (Карантин і захист рослин)
Goal. To carry out the analysis of phytosanitary risk for Ukraine of a dangerous quarantine pest Eutetranychus orientalis Klein (oriental spider mite).